High temperature thermally conductive nanocomposite textile by "green" electrospinning. Issue 35 (31st August 2018) - Wang, Jiemin; Li, Quanxiang; Liu, Dan; Chen, Cheng; Chen, Zhiqiang; Hao, Jian; Li, Yinwei; Zhang, Jin; Naebe, Minoo; Lei, Weiwei
Abstract : Recently, thermally regulating textiles have attracted wide interest owing to their ability to realize personal cooling and provide thermal comfort. Abstract : Recently, thermally regulating textiles have attracted wide interest owing to their ability to realize personal cooling and provide thermal comfort. However, most of the thermally conductive textiles cannot afford higher temperatures (>200 °C), which restricts their further applications in aviation, fire extinguishing or military requiring high temperature heat spreaders. Here, we report a high temperature thermally conductive nanocomposite textile consisting of amino functional boron nitride (FBN) nanosheets and polyimide (PI) nanofibers. Notably, the textile is "green" electrospun from aqueous solution without any toxic organic solvents, which is facile, economical and environmently friendly. Moreover, both FBN and the precursor of PI are modified to be water soluble and exhibit good compatibility in the spinning solution even under high concentrations. The "green" method obtained FBN-PI textile shows high thermal conductivity (13.1 W m −1 K −1 ) at a high temperature (300 °C), filling in the gap of thermally conductive polymer nanocomposite fibers for high temperature thermal regulation. Furthermore, it also provides efficient cooling capability as a thermal spreader. The good performance is ascribed to the weaving of the aligned FBN filament in a thermally stable PI fiber, which constructs an effective thermally conductive network. In addition, the nanocomposite textile is light weight, soft and hydrophobic, which is promising for electronic packaging or space suits for special high temperature thermal management.